Finite Element Analysys of the Deformation at Convex-Arc with Single-Point Mesh of Model 91 Gear with Double-Circular-Arc Tooth Profile - 綦耀光; 陈如恒; 丁全祥; 阎生群 (Jixie chuandong)
This paper discueses the finite element method of calculating deformation at convex-arc with single-point mesh of model gi gear with double-circulararc tooth profile and presents that the factors effecting the deformation is module,helix angle and coefficient of elasticity. Based on numerical analysis,the equations of calculating the deformation by regression are given. This is usful to analysis of the deformation and vibration of the gears.